PROFIL KYAI AHSIN SUYUDI DALAM MENGGEMBANGKAN PENDIDIKAN ISLAM DI PONDOK PESANTREN AL-ISHLAH MADIREDO - Ahsanul Muttaqin; Maskuri .; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Islamic boarding school certainly cannot be separated from the word kyai because kyai becomes one of the important elements in a boarding school. the problem or challenge that arises is whether pesantren in determining curriculum must adjust to the demands of the present day or be able to maintain the salifiah system as a characteristic of the pesantren pesantren into an institution that seeks to instill Islamic values in the world of students. Kyai Ahsin Suyudi is a Kyai figure who is close to the students, he is not only a teacher figure, but a father figure who can protect and give more attention to all his students. Kyai Ahsin Suyudi not only gave written and tausiyah lessons, he also provided education through role models in daily life which was a characteristic of his privilege, which is rarely done by most other dipesantren. In this study, researchers used qualitative research. With this type of case study research in collecting data researchers used the method of observation, documentation, and interviews. Data analysis methods used are data collection, data condensation, data presentation and conclusion drawing. From the results of the study showed that the cleric Ahsin Suyudi has a charismatic, democratic leadership type to shape people into pious people and character by way of studying the praahah, manaqib, weekly Koran, Kithobah, sublime taklim, binadhor with the lecture and yellow book models through the madrasah diniah.